ANOMALI MEDAN GRAVITASI PERMUKAAN (G) AKIBAT GERHANA MATAHARI SEBAGIAN (GMS) 9 MARET 2016 MENGGUNAKAN ANALISIS TRACKER PADA KATER’S REVERSIBLE PENDULUM - Fitri Nurul Sholihat; Suci Ramayanti; Anggi Hanif Setyadin; Ardi Rizkia Ferahenki; Muhamad Gina Nugraha; Duden Saepuzaman; Achmad Samsudin; Judhistira Aria Utama; Hana Susanti; Kartika Hajar Kirana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study was conducted to determine the gravitational field of the Earth's surface anomaly (g) due to the partial solar eclipse. Large gravity field of Earth's surface can be obtained using a pendulum swing period. Data were collected for three days on 8, 9, and 10 March, 2016 from at 6:00 to 9:00 pm in Bandung with coordinates 6°51'48 " LS, 107°35'40" BT. The tools used in this research was Kater's reversible pendulum with a deviation of less than 3° so that the motion can be regarded swing harmonics. Pendulum swinging motion is recorded using high resolution cameras (High definition) with a shooting speed  24 of frames per second (fps), the video is analyzed using the tracker in order to obtain the period of a pendulum swing. The results show the value of the gravitational field of the Earth's surface on a three-day consecutive sampling of 10,33153834, 10,18560435, and 10,32046468. According to the research there are anomalies in the gravitational field of the Earth's surface (g) due to the partial solar eclipse with the value of the gravitational field which decreases the time of the eclipse.Keywords: Eclipse, Tracker, Kater’s Reversible Pendulum.